Canadian bank notes and Dominion notes: Lessons for digital currencies - Ben Siu-cheong Fung; Scott Hendry; Warren E. Weber (Bank of Canada, 2017)
This paper studies the period in Canada when both private bank notes and governmentissued notes (Dominion notes) were simultaneously in circulation. Because both of these notes shared many of the characteristics of today's digital currencies, the experience with these notes can be used to draw lessons about how digital currencies might perform. The paper begins with a brief historical review of how these notes came into existence and of the regulations regarding their issuance. It examines historical evidence on how desirable bank notes were as media of exchange by examining how well they functioned with respect to ease of transacting, counterfeiting, safety, scarcity, and par exchange (a uniform currency). It then examines whether the introduction of government-issued notes improved how bank notes functioned as media of exchange. It finds that they did not. Improvements in the functioning of bank notes were due to changes in government regulation. Using the Canadian experience and that of the United States, the paper concludes that privately issued digital currencies will not be perfectly safe without government intervention, governmentissued digital currency will not drive out existing private digital currencies, and government intervention will be required for privately issued and government-issued digital currencies to be a uniform currency.
Keywords: E41; E42; E58; 330; Bank notes; Financial services; E-money